Consumer perceptions of community pharmacists' involvement in antimicrobial stewardship: A quantitative study - Kathryn Lim; Elaine Lum; Lisa Nissen; Alex Broom; Holly Seale (Elsevier, 2023)
Background Community pharmacist involvement in antimicrobial stewardship (AMS) within primary care is underutilised. Despite this view being consistently held across the pharmacy sector's policy, academic and professional spheres, there is limited understanding of how this positioning aligns with consumers' perceptions and expectations. Objective To explore participants' experience using antibiotics and their engagement with pharmacists to support their use. Methods Online survey of Australian adults recruited via Dynata's research panel in November 2022. Questions were organised into three sections: 1) understanding the participant's use of antibiotics, including their information needs; 2) exploring engagement with pharmacists on a cold and flu enquiry using a vignette question; and 3) demographic information. Results Doctors (42.0%), pharmacists (29.8%) and the internet including general searches (14.3%) were the top three sources for antibiotic information. Information about side effects and anticipated time to effect were more broadly sought from pharmacists than what was provided. Over 50% of respondents indicated alignment between the best practice example of a pharmacist providing cold and flu management advice with their own experience. 17% of respondents indicated that they would seek doctor's advice when considering cold and flu management options compared to 10% seeking pharmacist's advice. No statistically significant results between age groups or gender were observed. Conclusion Better visibility of community pharmacists' involvement in managing minor ailments in primary care, including more explicit linkage of pharmacist-administered vaccination services as an AMS strategy can support optimal antimicrobial use.